Macrophytes As Indicators Of The Ecological Status Of Valaam Island Small Lakes System - B. B. Buenano; N. V. Zueva (Geography, Environment, Sustainability)
The article evaluates the ecological status of five small lakes on Valaam Island (Igumenskoe, Chernoe, Ossievo, Nikonovskoe, Krestovoe) using macrophytes as bioindicators. The methods proposed by Finland, Sweden, and Norway were used, to assess the state of eutrophication, the change in the composition of specific species, the change in the water level, and the state of acidification, according to different indexes (Reference index (RI), Trophic Macrophyte Index (TMI), Trophic Index (TIc), the Proportion of Type– Specific Taxa (PTST), the Percent Model Affinity (PMA), Water level Index (WIc), and Acidification Index (SIc)). An analysis of the floristic composition for the period 2011 – 2020 was realized, including taxonomic analysis, ecogroup, and macrophyte diversity. The dominant taxon was Elodea canadensis Michx. in Igumenskoe, Chernoe, Ossievo lakes and Calla palustris L. in Nikonovskoe and Krestovoe lakes. The ecogroup hygrohelophyte was the most diverse in all lakes studied. The ecological status of the lakes according to each assessed parameter reflects that all lakes are characterized by a mesotrophic to eutrophic state, there is a variation in species composition of macrophyte and no water level change or acidification processes are presumed to occur in any of the lakes. In general, each method has its limitations, but it is suggested to continue studies for the RI, TMI, PTST, and PMA indices, and to integrate them with other national physicochemical or biological indices.